2015
DOI: 10.1371/journal.pone.0136991
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mesenchymal Stem Cell Therapy for Steroid-Refractory Acute Graft-Versus-Host Disease following Allogeneic Hematopoietic Stem Cell Transplantation: A Systematic Review and Meta-Analysis

Abstract: BackgroundMesenchymal stem cells (MSCs) have been broadly used experimentally in various clinical contexts. The addition of MSCs to initial steroid therapy for acute graft-versus-host disease (aGVHD) may improve patient outcomes. However, investigations regarding prognostic factors affecting the efficacy of MSC therapy for steroid-refractory aGVHD remain controversial. We thus conducted a systematic review and meta-analysis of published clinical trials to determine possible prognostic factors affecting the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 51 publications
2
42
0
2
Order By: Relevance
“…However, children showed a trend towards better CR compared with adults [25, 28]. Certain factors, including skin involvement and lower aGvHD grade, yielded a higher response rate to MSC application [25].…”
Section: Mscs In the Treatment Of Agvhdmentioning
confidence: 99%
See 1 more Smart Citation
“…However, children showed a trend towards better CR compared with adults [25, 28]. Certain factors, including skin involvement and lower aGvHD grade, yielded a higher response rate to MSC application [25].…”
Section: Mscs In the Treatment Of Agvhdmentioning
confidence: 99%
“…However, children showed a trend towards better CR compared with adults [25, 28]. Certain factors, including skin involvement and lower aGvHD grade, yielded a higher response rate to MSC application [25]. Possibly, inconsistent results of clinical studies are attributable to different or inconsistent pharmacological quality of MSCs resulting from the lack of a standardized methodology for MSC generation, dosing, and interdonor heterogeneity [5, 24].…”
Section: Mscs In the Treatment Of Agvhdmentioning
confidence: 99%
“…Median time to resolution of aGVHD is 30-42 days. in patients who respond to initial therapy, short-term tapering treatment with prednisone to a cumulative dose of 2,000 mg/m 2 is effective and expected to minimize steroid-related complications (71,72).…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Chen and colleagues summarized the results of 13 studies with a total of 301 pediatric and adult patients and report an overall response rate (complete and partial remissions) after MSC treatment for steroid-refractory acute GvHD in 205 patients (66%) (45). According to these review patients with skin steroid refractory acute GvHD showed a better response than patients with gastrointestinal (P<0.05) or hepatic (P<0.05) steroidrefractory acute GvHD.…”
Section: Box 2 Effects Of Mscs On Acute Gvhd Symptoms In Different Stmentioning
confidence: 99%